COLONIZATION AND ANTIBIOTIC RESISTANCE DYNAMICS OF PATIENTS AT INTENSIVE CARE UNIT (ICU)-OUR EXPERIENCE - Behera, Ishwar Chandra; Swain, Santosh Kumar; Sahu, Mahesh Chandra (Asian Journal of Pharmaceutical and Clinical Research, 2017)
introduction: Multidrug resistant strains are developed day by day due to empirical therapy in intensive care unit (ICU). Both gram positive and gram negative strains are found in ICU are drug resistant bacteria. In this study, the prevalence of drug resistance bacteria in ICU were determined. Materials and Methods: The clinical samples; ascitic fluid, blood, central line tip, ET aspirationÂ pleural fluid, pus from liver abscess, sputum, tracheal aspiration, urine and wound swabs were collected from ICU patients and cultured in specific medium. Subsequently antibiotic sensitivity pattern of isolated bacteria were carried out with disc diffusion methods. Results: A total number of 794 clinical samples were cultured in specific medium and it revealed 191 of single colonies, 145 were double colonies and 87 were 3 or multy-colonies. A total of 963 bacteria were isolated among them 180 were gram positive bacteria, BYC were 135 and rest were gram negative bacteria. There was no significantly difference in growth of microorganisms with respect to clinical samples as t test revealed P= 0.87. Among the gram negative bacteria; Klebsiela pneumonia were predominant and Proteous mirabilis was lowest. Tigecycline and colistin were most effective antibiotics agonist all bacteria. Conclusions: Urine samples of the patient's revealed higher number of organisms where as pus from liver abscess found only one number of growths. The antibiotic stewardship programs must lead to significant decrease in all antibiotic used in the ICU setting. However, this result may be required further work to determine the fruitful necessary for success. Key words: Antibiotics, Intensive Care Unit, Bacterial infections, Drug resistance.